Malaria and Related Haemosporidian Parasites of Wildlife in Southeast Asia: A Risk for Global Health - Khairani, Shafia; Setyowati, Endang Yuni; Krissanti, Ita (Jurnal Medik Veteriner, 2025)
Malaria and related haemosporidian parasites are widespread diseases that can inflict severe harm on both humans and animals. These parasites are protozoans classified within the order Haemosporidia, which encompasses four families: Garniidae, Haemoproteidae, Leucocytozoidae, and Plasmodiidae. The majority of species belong to three primary genera—Haemoproteus, Leucocytozoon, and Plasmodium—which have the capacity to infect a diverse array of animal species, including birds, reptiles, snakes, and mammals. Diagnostic techniques, such as light microscopy and molecular methods like polymerase chain reaction (PCR), have been extensively developed to identify these infections. Despite these advancements, research on the prevalence of malaria in wildlife across Southeast Asia remains sparse. This review article examines the significance of malaria and related haemosporidian parasites in wildlife within Southeast Asia and their potential implications for global human health. A total of 285 articles were reviewed, with 42 qualitative studies being included in this analysis. The majority of these studies were conducted in Malaysia, Indonesia, Thailand, the Philippines, Singapore, Myanmar, Laos, and Cambodia. Among the reviewed studies, 27 out of 42 (64.28%) focused on non-human primates, while 15 out of 42 (35.71%) addressed other wildlife such as birds and bats. Macaca fascicularis (long-tailed macaque) was the primary subject in 18 studies (66.66%), followed by M. nemestrina, Pongo pygmaeus, and various other macaque species and gibbons. In contrast, studies involving other wildlife, including birds and bats, exhibited considerable variability in species and sample sizes, ranging from a minimum of 4 individuals to a maximum of 400 individuals. Molecular diagnostics are predominantly used for non-human primates and other wildlife, as opposed to conventional methods like blood smears. Zoonotic malaria has emerged as a significant concern due to factors such as deforestation, agricultural expansion, and forest fragmentation, which increase human-wildlife interactions and facilitate mosquito breeding, thereby heightening the risk of Plasmodium knowlesi malaria. In summary, malaria and related haemosporidian parasites represent a substantial public health threat in Southeast Asia.